1952
DOI: 10.1039/jr9520004675
|View full text |Cite
|
Sign up to set email alerts
|

911. A new reaction of aliphatic diazo-compounds

Abstract: showed that aliphatic diazocompounds do not combine with tertiary amines as they do with phosphines; diphenyldiazomethane when heated with triethylamine undergoes the same decomposition to benzophenone azine as when heated in other solvents. If the first product of decomposition of the diazo-compound is the uncharged diphenylmethylene radical Ph&, it is conceivable that this will co-ordinate, reversibly, with the amine, giving Ph,C-NEt,, although in the end its fate is to combine with unchanged diazo-compound,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1955
1955
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In the 1952 article, Bamford‐Stevens proposed a plausible mechanism for the reaction, which is widely accepted now [1] . It was supposed that the diazo‐compound is always a primary product, as shown in Figure 1.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1952 article, Bamford‐Stevens proposed a plausible mechanism for the reaction, which is widely accepted now [1] . It was supposed that the diazo‐compound is always a primary product, as shown in Figure 1.…”
Section: Mechanismsmentioning
confidence: 99%
“…Bamford‐Stevens reaction was discovered in 1952 [1] . It was developed based on earlier results published by Escales who found that benzenesulphonylphenylhydrazide decomposes to benzene after treatment with warm alkali [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The second series of diazoketones 2a-e was prepared using a modified approach, which involved nitrosation 21 of monoketones 6a-e followed by conversion of the resulting α-diketones 7a-e into tosylhydrazones 9a-e accompanied by the Bamford-Stevens reaction. 7,22 Nitrosation of ketones 6a-e was carried out with sodium nitrite in the presence of concentrated hydrochloric acid. In fact, it involved a two-stage process -initial formation of oximes 10a-e followed by their hydrolysis under the reaction conditions to furnish α-diketones 7a-e.…”
Section: Syn Thesismentioning
confidence: 99%
“…The final stage of the synthesis of diazoketones 2a-f was the Bamford-Stevens reaction, which usually involves alkaline cleavage of 4-toluenesulfonyl hydrazones at elevated temperatures with strong bases, such as metal alkoxides, and others. 7,22 This process does not often stop at a stage of formation of diazo compounds, but leads to their decompo-sition with formation of by-products -alkenes, N-alkylated tosylhydrazones, etc. -generated via intermediate carbenes and/or carbenium ions.…”
Section: Scheme 2 Synthesis Of Tosylhydrazone 9fmentioning
confidence: 99%
“…Treatment of diaryldiazoalkanes with haloforms and base afforded azines [21] and alkenes [22] in variable amounts (59). Only alkenes [24] were obtained from organophosphorussubstituted diazoalkanes [23] with the dihalocarbenes generated from PhHgCCl 2 Br, PhHgCClBr 2 , and PhHgCBr 3 (60). The base-induced elimination of HX from derivatives of ethynylcarbinols (Chapter 4, Section V) in the presence of diaryldiazomethanes produced the corresponding cumulenes in 5-26% yield (60a).…”
Section: Diazo Compoundsmentioning
confidence: 99%